(untitled) (De Musica, 2023)
In his work Erscheinungsdinge. Aesthetik als Phaenomenologie (2010), Guenter Figal brings hermeneutical aesthetics back to phenomenology. Art cannot be reduced to philosophical truths. On the contrary, it is the manifestation of beauty. Artworks are appearences that simply show themselves. They show in them and with them a decentered order that stands for itself as an appearence. The present paper focuses on Figal’s philosophy of art from a musicological point of view. The main objective is to understand how a musical work can be an appearence that in its phenomenological structures shows itself as a decentered order. In this critical examination some crucial questions arise. Is indeed the musical work a thing (Ding) or is it an acoustic phenomenon? Can the rhythmic play be considered as the musical form par excellence? Which are the relationships between music and space?